Reducing patient–staff contact in fast-track total hip arthroplasty has no effect on patient-reported outcomes, but decreases satisfaction amongst patients with self-perceived complications: analysis of 211 patients - Hansen, Jens B; Sørensen, Jens F L; Glassou, Eva N; Homilius, Morten; Hansen, Torben B (Acta Orthopaedica, 2022)
Background and purpose: Several studies have compared fast-track with conventional pathways for total hip arthroplasty (THA) patients, but none have compared different fast-track pathways. Due to COVID-19 restrictions, our department had to minimize patient–staff contact in the THA pathway. First, telephone consultations were implemented instead of an outpatient clinic visit and subsequently preoperative patient education was discontinued. This enabled us to compare patient-reported outcomes and satisfaction among 3 fast-track pathways. Patients and methods: We collected data from patients treated for hip osteoarthritis with THA at Gødstrup Hospital between 2018 and 2021. The patients had experienced 1 of 3 pathways and were interviewed via telephone between 2 and 6 months after discharge. We analyzed the influence of patient pathway on patient-reported pain and mobility level, self-perceived complications, and compliance using logistic regression. We then compared the pathway’s effect on patient satisfaction both for the total sample and for the patients who experienced complications. Results: The amount of patient–staff contact in the patient pathway did not have any influence on patientreported outcomes or the probability of self-perceived complications. For the full sample, patient–staff contact had no statistically significant influence on patient satisfaction either, but for the subgroup of patients experiencing complications, the pathways with less patient–staff contact reduced satisfaction. Patient satisfaction was primarily related to pain and mobility outcomes. Interpretation: Our results indicate that reducing patient–staff contact in fast-track THA can be done without influencing mobility and pain outcomes, but the overall satisfaction among patients with self-perceived complications will be negatively affected.